ANALISIS KESALAHAN EJAAN MAKALAH MAHASISWA ILMU KOMPUTER UNWIRA KUPANG - Agung, Giovanni Battista (Universitas Hamzanwadi, 2025)
This study aims to describe the types of spelling errors found in the academic papers written by second-semester students of the Computer Science Study Program at Widya Mandira Catholic University. The research focuses on three key aspects outlined in the General Guidelines for Indonesian Spelling (EYD), 5th edition: the use of capital letters, punctuation marks, and word formation. Employing a qualitative approach with a descriptive method, data were collected using documentation techniques by identifying and transcribing relevant sections from five purposively selected student papers. The data were analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The results indicate that spelling errors remain a recurring and dominant issue in students’ academic writing. These errors consistently appear across the analyzed documents, including the omission of capital letters in proper nouns and sentence-initial positions, incorrect use of punctuation that affects sentence structure and clarity, as well as errors in the use of prepositions, reduplication, and nonstandard word forms. These findings reflect students’ limited mastery of spelling conventions and a lack of revision or proofreading habits. This study emphasizes the importance of strengthening Indonesian language instruction by focusing on practical writing and editing skills, especially within non-language academic programs.